A round-up of dosing, mixing & other equipment innovations from K 2019. Issue 11 (November 2019) - Unknown
Abstract : At October's giant plastics trade fair K 2019, a number of equipment makers highlighted their latest offerings appropriate for the preparation, dosing and handling of polymer additives, colorants and masterbatches.